The Dualism of Reconciliation Law After Triple Talaq Outside the Court - Nita Azita Zein; Imam Yazid; Heri Firmansyah (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2023)
Revocation of divorce (ruju’) generally occurs after a husband's first or second pronouncement of divorce (talaq). However, after the third pronouncement (third talaq), Islamic jurisprudence (fiqh) prohibits revocation unless specific conditions are met. This study examines the legal dualism regarding rujuk after third talaq, especially when talaq is pronounced outside the Court. Unlike the four major fiqh schools, Indonesian law requires talaq to be declared in a Religious Court session, as stated in Article 5, Paragraph (1) of the Compilation of Islamic Law. This research aims to comprehensively understand the dualism of the reconciliation law after divorce that often occurs outside the Court. Using normative legal research with a qualitative approach, the findings suggest that Muslims should pronounce talaq and ruju’ in front of a Religious Court to comply with Indonesian law and ensure legal protection and administrative recording of marriage and divorce. The study recommends that the Religious Court consider talaq pronounced outside the Court if substantiated with witness testimony.